2022
DOI: 10.1001/jamanetworkopen.2022.39778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Safety Outcomes of Neoadjuvant Immunotherapy Combined With Chemotherapy for Patients With Resectable Esophageal Cancer

Abstract: ImportanceA considerable number of clinical trials of neoadjuvant immunotherapy for patients with resectable esophageal cancer are emerging. However, systematic evaluations of these studies are lacking.ObjectiveTo provide state-of-the-art evidence and normative theoretical support for neoadjuvant immunotherapy for locally advanced resectable esophageal cancer.Data SourcesPubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases were searched for relevant original articles and conference proceedings th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 87 publications
0
20
1
Order By: Relevance
“…The neoadjuvant immunotherapy significantly improved pCR rates with tolerable toxicity in EC patients (14)(15)(16)(17). However, the best neoadjuvant treatment strategy for EC was still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neoadjuvant immunotherapy significantly improved pCR rates with tolerable toxicity in EC patients (14)(15)(16)(17). However, the best neoadjuvant treatment strategy for EC was still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of neoadjuvant ICIs combined with nCT has been previously reported in esophageal cancer ( 12 , 13 ). Recent meta-analyses have demonstrated the neoadjuvant ICIs combined with nCT or nCRT had promising clinical result and acceptable safety outcomes for patients with locally advanced EC ( 14 17 ). Nevertheless, there was no any meta-analyses comparing neoadjuvant ICIs combined with nCT or nCRT with routine neoadjuvant therapy, which included nCRT and nCT.…”
Section: Introductionmentioning
confidence: 99%
“…Following the launch of a new era in immunotherapy (including programmed cell death-ligand 1 [PD-L1] and programmed cell death protein-1 [PD-1] inhibitors), further exploration of neoadjuvant immunotherapy alone or combined with chemotherapy or chemoradiotherapy is expected to further improve the therapeutic effect in locally advanced resectable ESCC. In a recent systematic review including 27 phase 2 or 3 clinical trials with 815 patients, the pooled pathological complete response (pCR) rate was 32.4% in ESCC after neoadjuvant chemoimmunotherapy(nCIT), with the pooled incidence of treatment-related severe adverse events of 26.9% (7). Zhu et al reported that neoadjuvant immunochemoradiotherapy could not improve the pCR rate than neoadjuvant chemoradiotherapy (nCRT) for ESCC, but significantly increased the risk of severe adverse events (8).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, neoadjuvant targeted therapy and immunotherapy have become new trends in preoperative adjuvant therapy for malignant tumors and have broad application prospects [5,[11][12][13][14][15]. However, owing to high price, uncertainty (still in clinical tails), and restriction (targeted and biologic therapies account for only 30% of all rst-line treatments), platinum-based chemotherapy regimens remain a rst-line treatment option or one of the components of neoadjuvant or adjuvant therapy for most of the cancers.…”
Section: Introductionmentioning
confidence: 99%